Knemidokoptic mite infections on the Cape Peninsula population of Black Sparrowhawks - Van Velden, Julia (Department of Biological Sciences, 2014)
Knemidokoptes mites (Acari: Knemidokoptidae) are subcutaneous mites that are found in the skin of the face, legs or body of avian hosts, the symptoms of which can range from featherloss and skin lesions to beak deformities. Although known to infect multiple species of Passeriform birds, very few cases have ever been reported in birds of prey. An unusually high number of Black Sparrowhawks of the Cape Peninsula were identified as being affected by these mites, with obvious symptoms such as baldness and leg lesions. This is the first record of a possible epizootic event caused by Knemidokoptic mites in a wild population of a bird of prey. The number of infection cases elsewhere in South Africa was surveyed and it was found that only rare single cases have been reported, meaning that some causal factor is driving the high infection rate in the Cape Peninsula, where a maximum of 5% of the breeding population were recorded as infected in any one year. The subclinical level of this infection was found to be low, with most of the population not having any mites and only a few individuals representing clinical cases. The infections affect on individual fitness was explored and it was found that it had a significant negative effect on breeding success (p<0.05) and productivity (p<0.01), but I was unable to preform a survival analysis, due to lack of data. A male bias in infections was detected, but there was no difference in the probability of infection and the morph of the bird in this polymorphic species. These results therefore suggest that this infection has the potential to affect the stability of this population over time, due to its effect on reproductive success. Although this species is not endangered, this possible epizootic event is of interest to the study of bird-parasite systems, specifically how this study ectoparasite can negatively affect the fitness of their hosts.